Epidemiology, clinical characteristics, and associated cost of acute poisoning: a retrospective study - Waleed Salem (19794156) (2024)
Introduction Poisoning is a major public health issue and a leading cause of admission to the emergency department (ED). There is a paucity of data describing the epidemiology and cost of acute poisoning. Therefore, this study investigated the epidemiology, patterns, and associated costs of acute poisoning in emergency department of the largest tertiary care healthcare centre in Qatar. Method This study was a retrospective review of the health records of patients admitted to the ED due to poisoning between January 2015 and December 2019. Incidence, clinical characteristics, and costs associated with acute poisoning were assessed. Frequency and percentages were calculated for categorical variables and mean and SD for continuous variables. The relationship between sociodemographic characteristics and poisoning profile was assessed using the chi-square test. A micro-costing approach using the cost of each resource was applied for cost calculations. Result The incidence of acute poisoning was 178 cases per 100,000 patients. Females (56%) and children below 14 years (44.3%) accounted for the largest proportion. Most of the exposures were accidental involving therapeutic agents (64.2%). The mean length of hospital stay was found to be 1.84 ± 0.81 days, and most patients (76.6%) were discharged within the first 8 h. A statistically significant difference was found between age groups and type of toxin (χ2 = 23.3, p < 0.001), cause and route of exposure (χ2 = 42.2, p < 0.001), and length of hospital stay (χ2 = 113.16, p < 0.001). Admission to intensive care units had the highest cost expenditure (USD 326,008), while general wards accounted for the least (USD 57,709). Conclusion Unintentional poisoning by pharmacological agents is common in infants and children. This study will assist in the development of educational and preventive programmes to minimise exposure to toxic agents. Further studies are required to explore the impact of medical toxicology services, and post discharge monitoring of poisonin Other Information Published in: Journal of Pharmaceutical Policy and Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/20523211.2024.2325513